Review of the azurescens-group, with the description of six new brachypterous species of Stenus Latreille, 1797 from the Philippines (Coleoptera, Staphylinidae, Steninae) - Tobias Mainda (Soil Organisms)
Here, the endemic species group of the rove beetle Stenus azurescens L. Benick, 1929 in the genus Stenus Latreille, 1797 from the Philippines is reviewed. Six new species are described: S. rolandmuelleri spec. nov. (Negros), S. hamiguitanensis spec. nov. (Mindanao), S. alexi spec. nov. (Mindanao), S. alexeyi spec. nov. (Mindanao), S. circumspector spec. nov. (Mindanao) and S. cuprifulgens spec. nov. (Mindanao). In addition, an identification key is published with which all taxa of the azurescens-group can be identified to species level.